Utilization of Artificial Intelligence in Predicting Crime - Carissa, Joan Stacia; Turnip, Mardi (Information Technology and Science (ITScience), 2024)
The problem of crime in Indonesia is an urgent issue, with crime rates continuing to increase. High crime rates have serious impacts on societal security, social stability, and economic development. Amidst the complexity of types of crime, motives and methods of handling them, Artificial Intelligence (AI) and Machine Learning (ML) technology has emerged as a promising solution. Through analysis of a literature review with the keywords